Nutrient dynamic in sediment and organs of the mangrove Avicennia marina (Forsk.) Vierh - Ariyanto Dafit; Pringgenies Delianis; Natalia Br Ginting Devica (BIO Web of Conferences)
Avicennia marina is a mangrove species that can be found on the coast of Indonesia, specifically in Lampung province. The aim of this study was to investigate the relationship between Avicennia marina nutrients in natural mangroves. This study was conducted in the coast of Pesawaran, Lampung, Indonesia in December 2023. Nutrient sampling included leaves, roots, and sediment in the Avicennia marina mangrove area. The statistical analysis used the principal component analysis (PCA) approach. The nutrients analyzed were nitrogen (N), phosphorus (P), zinc (Z), magnesium (Mg), and iron (Fe) in the leaves, roots, and sediment. The results of this study revealed the eigenvalues and loading factors of the nutrient variables. The main factor (F1) presented 99.78% of the variable data where each variables contributed not significantly different. The main to the least variables were Mg (0.47), Fe (-0.46), N (0.43), Zn (-0.43), and P (0.42). The negative values of Fe and Zn variables indicated a negative correlation with Mg, N, and P. If the Fe and Zn values increase, then the Mg, N, and P values will be the opposite.